Penerapan Buerger Allen Exercise Pada Pasien Risiko Luka Kaki Diabetes Melitus Dengan Masalah Keperawatan Risiko Perfusi Perifer Tidak Efektif - Alex Atmasubrata; Fitri Afdhal; Muhammad Romadhon; Indra Frana Jaya KK (JURNAL KESEHATAN TERAPAN, 2026)
Diabetes mellitus is a chronic metabolic disease characterized by increased blood glucose levels due to impaired insulin secretion or action, which can lead to ineffective peripheral perfusion. This study aimed to determine the effect of Buerger Allen Exercise (BAE) on peripheral perfusion in patients with diabetes mellitus at risk for ineffective peripheral perfusion. The study used a descriptive method with two respondents who met the inclusion criteria in the inpatient ward of X Hospital, South Sumtera. Client 1 received Buerger Allen Exercise (BAE) twice daily for three days, while Client 2 was only observed. Measurement of the Ankle Brachial Index (ABI) showed an increase from 0.7 to 1.0 in Client 1, accompanied by warmer skin and reduced numbness. Client 2 showed no significant change. It can be concluded that Buerger Allen Exercise (BAE) is effective in improving peripheral perfusion in patients with diabetes mellitus.